Eksplorasi Pemecahan Masalah Ditinjau Dari Tingkat Koneksi Matematis Yang Dibangun Oleh Mahasiswa STKIP YPUP Makassar - Nurfaida Tasni (Fakultas Keguruan dan Ilmu Pendidikan Univ. Al Asyariah Mandar Sulbar, 2017)
The purpose of this study is to explore problem-solving abilities based on the level of mathematical connections built by STKIP YPUP Makassar students. This research is a qualitative explorative research based on task-based interview. The subjects of the study were STKIP YPUP students who programmed linear courses. This type of problem is developed based on the characteristics of mathematical connections according to NCTM, ie connections between mathematical topics, connections with other disciplines, and connections in everyday life. Data collection was done through semi-structured interview process to 2 subjects selected by purposive sampling technique. The results showed by establishing a high connection then Students are able to perform the problem-solving process well.